Valdosta State University Football 2004 - Valdosta State University, Athletics Department (Valdosta State University, 2004)
The positive reputation of Valdosta State University athletics has grown by leaps and bounds in the 12-plus years Herb Reinhard has been in charge of the 11-sport Division II program. Reinhard joined the Valdosta State athletic family in December 1991, coming from Florida A&M University where he was assistant athletic director in charge of marketing and promotions.
### Staff 2004: Chris Hatcher; Shawn Bostick; David Dean; Ashley Anders; Ryan Shirley; Maurea Crain; Michael Doscher; Russ Hoff; Bobby Tucker; Lori Howard; Chuck Conner; Debi Frocks; Steve Roberts; ### Players 2004: Jeffrey Felton; Willie Johnson; Raymond Thomas; Tyler Aurandt; Chad Gallahan; Bama Adams; Fabian Walker; Donnie Danie; Kenn Barnett; Barrett Wilkes; Fred Dunn; Vincent Brow; Clay Callaway; Mitch Stewart; Rod Dalton; Tyran Robinson; Darrell Stephens; Scott Foss; Kevin Adkins; Michael Flood; William Milton; Latray Walker; Will Rhody; Travis Taylor; Donald Thomas; Sam Reynolds; Antwan Harris; Tyler Pruitt; Scott Palmer; Spencer Fortson; Sam Brown; Gio Blalock; Calvin Roberts; Oscar Patterson ; Javaris Weston; Travis Tidwell; Dedrick Morrison ; Michael Green; Nate Hardge; Cody Thomas; Stephen Delk; Phillip Braley; William Montford; Antwan Thomas; Davis Russell; Robert Summers; Matt Tanner; John Harrison; Toe Massingill; Gerald Davis; Torrey Howard; Paul Streaker; Patrick Brantley; Josh Bennett; Chris Crosby; Jos Edison; Davis Nall; William Shelton; Leighton Cooley; Joseph Lord; Richard Collier; Kelvin McDavis; Terel Toomer; Marcellus Washington; Robert Broughton; Tommy Parker; Chad Bryant; Pat Wolfe; Zach Parker; Drew Willis; Dustin DeHaven; Derek Cosby; Tim Thompson; James Hutley; Fabian Whylly; Tracy Flounoy; Derrick Hill; Calvin English;
Keywords: Athletics; Football